2010
DOI: 10.1021/nn101883s
|View full text |Cite
|
Sign up to set email alerts
|

Viscous State Effect on the Activity of Fe Nanocatalysts

Abstract: C atalytic chemical vapor deposition (CVD) is an effective site/sizeselective synthesis technique. 1Ϫ7The properties of the catalytic particle play a key role in the nucleation and growth processes, as well as in the final nanostructure morphology. 7Ϫ11 At the nanoscale, two aspects are inter-related: the possibility of bulk and surface diffusion of the feedstock in and on the nanoparticles 12Ϫ14 and the thermody- Here, we analyze the nanoparticles near the melting point by investigating, as functions of size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
(139 reference statements)
2
16
0
Order By: Relevance
“…Many authors reported that the growth rate of nanotubes increases with decreasing the size of catalyst particles. This trend was observed in the synthesis processes using different catalysts: Ni, Co, Fe [181], Co [97], Ni [182183] and Fe [184185]. For example, the authors of [183] showed that the growth rate of nanotubes in the CVD synthesis using nickelocene as catalyst precursor and C 2 H 2 as carbon source increased by a factor of 3 while decreasing the size of Ni catalyst particles from 3.1 to 2.2 nm.…”
Section: Reviewmentioning
confidence: 72%
“…Many authors reported that the growth rate of nanotubes increases with decreasing the size of catalyst particles. This trend was observed in the synthesis processes using different catalysts: Ni, Co, Fe [181], Co [97], Ni [182183] and Fe [184185]. For example, the authors of [183] showed that the growth rate of nanotubes in the CVD synthesis using nickelocene as catalyst precursor and C 2 H 2 as carbon source increased by a factor of 3 while decreasing the size of Ni catalyst particles from 3.1 to 2.2 nm.…”
Section: Reviewmentioning
confidence: 72%
“…Many growth models predict that the nanotube growth rate will either increase [343,344] or decrease [330] with diminishing size of the catalyst particle. For instance, the model proposed by Puretzky et al [330] stipulates that the larger diameter nanotubes should grow faster than the smaller diameter ones due to their higher surface area to circumference ratio.…”
Section: Growth Ratementioning
confidence: 99%
“…2 of Ref. [58]), to study trends of solubility and size-dependent disorder-order transitions and segregation in nanocatalysts [21,[58][59][60] and nanocrystals [61,62].…”
Section: Discussionmentioning
confidence: 99%